AN ANALYTICAL STUDY OF AWARENESS AND PERCEPTION TOWARDS GST AMONGST TRADERS IN RURAL AREAS - Sahayaraj, Dr.M. Vincent; Kalaiselvan, Dr.D. (IJRDO - Journal of Business Management, 2017)
The overture of Goods and Services Tax (GST) would be a very momentous step in the field of indirect tax. Goods and Services tax (GST) has been acknowledged as one of most imperative tax reform post-independence. It is a tax trigger, which will lead to business transformation for the industry. State assemblies, the Government of India give the impression to be on way to implement GST with effect from 1 July 2017. The sizeable efforts by the Government machinery to introduce the reforms at the earliest are worth appreciable but at the same time with stiffer deadlines it seems that government is in haste to implement this reforms at the earliest which may be paralyzed by lack of information and orientation of small traders in rural areas who form a sizeable community of traders. The study aims to be familiar with the perception towards existing Tax System, awareness of GST among the traders of different categories and their turnovers with problems and challenges. It is reported that the lack of information coupled with the apathy towards reforms may paralyze the speedy implementation of this system especially in small towns where still not a single orientation programs have been planned and executed till date by competent authorities. Further it is observed that neither business type or its legal status affect the opinion regarding opinion towards GST but business turnover seems to be associated with the opinion regarding present tax administration system with business having higher turnover reporting greater disappointment with present system.In lien of this it is suggested associations, NGO’s should come forward to organize such programs at town level to orient small traders so that nobody is left out of this biggest tax reform in the country.